2011
DOI: 10.1371/journal.pone.0021696
|View full text |Cite
|
Sign up to set email alerts
|

SHARPIN Negatively Associates with TRAF2-Mediated NFκB Activation

Abstract: NFκB is an inducible transcriptional factor controlled by two principal signaling cascades and plays pivotal roles in diverse physiological processes including inflammation, apoptosis, oncogenesis, immunity, and development. Activation of NFκB signaling was detected in skin of SHAPRIN-deficient mice and can be diminished by an NFκB inhibitor. However, in vitro studies demonstrated that SHARPIN activates NFκB signaling by forming a linear ubiquitin chain assembly complex with RNF31 (HOIP) and RBCK1 (HOIL1). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…It has been recently shown that NSP1α protein from highly pathogenic PRRSV-2 inhibited NF-kB activation by targeting the linear ubiquitin chain assembly complex (LUBAC) composed by the SHARPIN, HOIP, and HOIL-1L subunit ( 66 ). In particular , SHARPIN has been associated with NFkB activation and described as essential for cytokine production and induction of Th1 differentiation by DC ( 67 , 68 ). In our data, SHARPIN was up-regulated in vitro by Lena infection but was consistently down-regulated by FL13 both in vivo (PIM, moDC, and cDC1 and 2) and in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that NSP1α protein from highly pathogenic PRRSV-2 inhibited NF-kB activation by targeting the linear ubiquitin chain assembly complex (LUBAC) composed by the SHARPIN, HOIP, and HOIL-1L subunit ( 66 ). In particular , SHARPIN has been associated with NFkB activation and described as essential for cytokine production and induction of Th1 differentiation by DC ( 67 , 68 ). In our data, SHARPIN was up-regulated in vitro by Lena infection but was consistently down-regulated by FL13 both in vivo (PIM, moDC, and cDC1 and 2) and in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cell type–specific functions for HOIL-1L, the LUBAC subunit Sharpin may also have tissue-specific roles. It has been reported that Sharpin cpdm MEFs ( Gerlach et al, 2011 ; Ikeda et al, 2011 ; Tokunaga et al, 2011 ) and BMDMs ( Zak et al, 2011 ) have defects in NF-κB signaling, yet skin cells from Sharpin cpdm mice have elevated NF-κB activation ( Liang, 2011 ; Liang et al, 2011 ), suggesting that Sharpin has unique functions in skin cells. In fact, the dermatitis phenotype observed in Sharpin cpdm mice is reversed by NF-κB inhibitor treatment ( Liang et al, 2011 ) or knockout of the TNF gene ( Gerlach et al, 2011 ), further supporting cell type–dependent roles for Sharpin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cell type-specific functions for HOIL-1L, the LUBAC subunit Sharpin may also have tissue-specific roles. It has been reported that Sharpin cpdm MEFs (Gerlach et al, 2011;Ikeda et al, 2011;Tokunaga et al, 2011) and BMDMs (Zak et al, 2011) have defects in NF-B signaling, yet skin cells from Sharpin cpdm mice have elevated NF-B activation (Liang, 2011;Liang et al, 2011), suggesting that Sharpin has unique functions in skin ASC. However, our attempts to map the ubiquitinated residues of ASC indicate that mutagenesis of the lysines in ASC affects protein-protein interactions independently of linear ubiquitination, making finer evaluation of the role of ASC linear ubiquitination for inflammasome activation difficult.…”
Section: Role Of Hoil-1l In Nlrp3-induced Il-1 Production and Inflammation In Vivomentioning
confidence: 99%
“…A yeast two-hybrid (Y2H) screen with TRAF2 (TNF receptor-associated factor 2) as the bait (UCSD Nature Signaling Gateway, data center, yeast two-hybrid, http://www.signaling-gateway.org/data/Y2H/cgi-bin/y2h _int.cgi?id=53738 ) has identified SHARPIN (alternative symbol: protein kinase C-interacting protein RBCC like 1 (RBCKL1)) is one of its preys in B cell lines. Protein immunoprecipitation identified SHARPIN has interaction with TRAF2 and negatively regulates TRAF2-mediated NF κ B activity [ 17 ]. Inhibition of NF κ B signaling can significantly alleviate the skin problems in Sharpin cpdm mice [ 14 ].…”
Section: Introductionmentioning
confidence: 99%